Constitutional Law Around the Globe: Fundamental Rights, the Freedom of Speech and “Hate Speech” in Canada - Araujo, Luiz Henrique Diniz (Revista de Investigações Constitucionais, 2023)
This paper exploring the Freedom of Speech in Canadian Constitutional Law is part of the series “Constitutional Law Around the Globe”. This chapter of the series focuses on “Fundamental Rights and Freedom of Speech” in contemporary democracies. Second in the row, this paper analyses the Freedom of Speech in Canadian Constitutional Law and how it has been shaped by the Supreme and lower courts over time, specially on the so-called “hate speech”. A final paper will approach the legal systems composing the series in a comparative perspective.